Global Value Chain and Total Factor Productivity in Africa - Ajide, Folorunsho M. (Organizations and Markets in Emerging Economies, 2023)
This paper examines the impact of global value chain (GVC) participation on total factor productivity in African economies. The analysis is based on panel corrected standard errors, IV-estimation technique and the novel Method of Moment (MM)-panel quantile regression. The results reveal that there is positive and significant relationship between global value chain and total factor productivity in African economies. Specifically, we discover that the impact of GVC participation on total factor productivity is positive and significant. This result is consistent across all the quartiles after employing MM-panel quartile regression. The coefficients of global value chains improve as we approach a higher quantile. The study concludes that GVC participation allows access to a larger global market which local firms may explore to gain from scale economies, and to learn using modern technology and innovations. It facilitates connections to cheaper and quality inputs for domestic production, while efficiency is guaranteed.
Keywords: Africa; domestic added value; forward added value; MM-panel quartile regression